2020
DOI: 10.3389/fvets.2020.588173
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Application of Multiplex PCR for Simultaneously Detecting Escherichia coli, Salmonella, Klebsiella pneumoniae, and Staphylococcus aureus in Minks

Abstract: To establish a multiplex PCR for simultaneous detection of Escherichia coli ( E. coli ), Salmonella, Klebsiella pneumoniae ( K. pneumoniae ), and Staphylococcus aureus ( S. aureus ), four pairs of specific primers were designed according to the conservative regions of phoA gene for E. coli, invA gene for Salmonella, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…From current sensitivity results, the LOD of E. coli in our study was similar to the results previously reported [ 12 ], with a detection limit of 10 pg. Nogva et al performed PCR amplification using the HlyA gene of L. monocytogenes , and the results showed a detection limit of 1 pg of L. monocytogenes [ 31 ], similar to the results of the current experiment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From current sensitivity results, the LOD of E. coli in our study was similar to the results previously reported [ 12 ], with a detection limit of 10 pg. Nogva et al performed PCR amplification using the HlyA gene of L. monocytogenes , and the results showed a detection limit of 1 pg of L. monocytogenes [ 31 ], similar to the results of the current experiment.…”
Section: Discussionsupporting
confidence: 89%
“…Hernandez et al successfully detected 1~10 CFU of Shigella and Salmonella from food samples within 24 h at low detection limits [ 11 ]. Li et al also used multiplex PCR to detect the genomic DNA of four pathogenic bacteria with a detection limit of 100 pg/μL [ 12 ]. Ashraf et al successfully detected pathogenic bacteria from milk samples at a concentration of 10 4 CFU/mL [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional strength of the mPCR assays was its capability to detect DNA concentrations as low as 100 pg which was similar to the previous reports [ 29 , 30 ], although these targeted different pathogens. This outcome is attributable to the methodology of PCR that enables it to amplify small concentrations to readily detectable quantities.…”
Section: Discussionsupporting
confidence: 83%
“…A gene designated khe , which encodes a hemolysin of K. pneumoniae , has been proposed as a potential species-specific gene probe ( Yin-Ching et al, 2002 ) and was utilized to detect the signature for clinical K. pneumoniae isolates from hospitals ( Escobar Pérez et al, 2013 ; Chen et al, 2014 ; He et al, 2016 ). Li et al (2020) designed a multiplex PCR method to detect K. pneumoniae in minks with the khe gene. These studies suggested that khe is a specific gene of K. pneumoniae .…”
Section: Introductionmentioning
confidence: 99%